Kai Althoff - And then leave me to the common swifts = Kai Althoff - Und dann überlaßt mich den Mauerseglern - Naiditch, Dovber; Rothkopf, Constantin (The Museum of Modern Art, 2016)
"Published in conjunction with the exhibition 'Kai Althoff: and then leave me to the common swifts', presented at The Museum of Modern Art, New York, from September 18, 2016, to January 22, 2017"
Keywords: Althoff, Kai -- 1966-; Ausstellungskatalog -- The Museum of Modern Art -- 18.09.2016-22.01.2017 -- New York, NY; Bildband